2010
DOI: 10.1111/j.1465-3362.2010.00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes in methamphetamine psychosis patients after first hospitalisation

Abstract: Individuals with MAP are likely to have poor outcomes, in terms of premature death, several relapses of psychotic symptoms, chronic psychotic manifestation, and very rates of alcohol use disorder and suicidality. Therefore, those individuals with MAP require long-term monitoring and psychiatric care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 11 publications
(22 reference statements)
3
69
0
4
Order By: Relevance
“…A follow-up study in Thailand revealed that onequarter of patients with methamphetamine psychosis had been given the diagnosis of schizophrenia within the 5 years following their first hospitalization (48). Close monitoring for the development of chronic or recurrent psychosis among individuals with transient symptoms, possible pharmacological management of acute symptoms, and behavioral treatment and psychoeducation addressing methamphetamine use and its association with psychosis are needed.…”
Section: Methamphetamine Psychosismentioning
confidence: 99%
“…A follow-up study in Thailand revealed that onequarter of patients with methamphetamine psychosis had been given the diagnosis of schizophrenia within the 5 years following their first hospitalization (48). Close monitoring for the development of chronic or recurrent psychosis among individuals with transient symptoms, possible pharmacological management of acute symptoms, and behavioral treatment and psychoeducation addressing methamphetamine use and its association with psychosis are needed.…”
Section: Methamphetamine Psychosismentioning
confidence: 99%
“…Noen store og solide studier viser at en vesentlig andel av de pasientene som opprinnelig fikk diagnosen amfetaminutløst psykose, senere får diagnosen schizofreni. I en studie fra Asia fulgte man pasienter 6 -7 år etter første innleggelse for amfetaminutløst psykose og konkluderte med at 23 % av dem uten pågående amfetaminbruk fylte diagnosekriteriene for schizofreni (5). I en registerstudie fra Finland var det liknende funn -det var en åtteårs kumulativ risiko på 30 % for overgang fra amfetaminutløst psykose til schizofreni.…”
Section: Fra Rusutsløst Til Primaerunclassified
“…Many young people with psychosis abuse stimulant drugs (Hides et al, 2006;Sara et al, 2013) however most of these young people also abuse cannabis (Degenhardt et al, 2010b), making it difficult to separate the effects of these two drugs. In a large Thai sample, more than half of first admissions with specific diagnoses of methamphetamine psychosis went on to have further episodes of psychosis (Kittirattanapaiboon et al, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…South East Asian countries have high rates of methamphetamine use and researchers from these countries have contributed many of the studies examining the familial, genetic and pharmacological characteristics of methamphetamine-related psychoses (Bousman et al, 2009). Most of these studies use a diagnostic construct of "Methamphetamine Psychosis", which is seen as including both acute and transient psychotic states (Kittirattanapaiboon et al, 2010) and psychosis which persists or recurs despite abstinence from stimulants (Sato et al, 1992;Suzuki et al, 2006;Yamamoto et al, 2007;Yui et al, 2000a).…”
Section: The Overlap Between Cannabis and Stimulant Use Disordersmentioning
confidence: 99%
See 1 more Smart Citation